2012
DOI: 10.1136/jnnp-2012-302217
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cognitive impairment by the Montreal Cognitive Assessment in patients with aneurysmal subarachnoid haemorrhage: prevalence, risk factors and correlations with 3 month outcomes

Abstract: MoCA defined cognitive impairment was common at 3 months after aSAH and MoCA correlated with functional outcomes similar, but not superior, to the MMSE. The study is registered at ClinicalTrials.gov of the US National Institutes of Health (NCT01038193).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 33 publications
(32 reference statements)
2
73
0
2
Order By: Relevance
“…28 Two studies compared MoCA and MMSE 3 to 6 months after aneurysmal subarachnoid hemorrhage. 29,30 MoCA was more sensitive than MMSE in detecting PSCI in patients who had returned to work, and, unlike MMSE, correlated with performances on a comprehensive neuropsychological battery and with the functional outcome (Glasgow Outcome Scale). 29 Wong et al 30 examined the ability of MoCA and MMSE to differentiate favorable functional outcome (modified Rankin Scale, 0-2) and Instrumental Activities in Daily Living score in patients with postaneurysmal subarachnoid hemorrhage and found similar accuracy for both tests at their optimal cutoff values.…”
Section: Use Of Moca In the Chronic Poststroke Phasementioning
confidence: 99%
See 1 more Smart Citation
“…28 Two studies compared MoCA and MMSE 3 to 6 months after aneurysmal subarachnoid hemorrhage. 29,30 MoCA was more sensitive than MMSE in detecting PSCI in patients who had returned to work, and, unlike MMSE, correlated with performances on a comprehensive neuropsychological battery and with the functional outcome (Glasgow Outcome Scale). 29 Wong et al 30 examined the ability of MoCA and MMSE to differentiate favorable functional outcome (modified Rankin Scale, 0-2) and Instrumental Activities in Daily Living score in patients with postaneurysmal subarachnoid hemorrhage and found similar accuracy for both tests at their optimal cutoff values.…”
Section: Use Of Moca In the Chronic Poststroke Phasementioning
confidence: 99%
“…11 Similarly, Lees et al, 33 using the original cut-off of 26, diagnosed cognitive impairments in 86% of acute stroke unit patients; the proportion decreased to 49% if the cut-off was decreased to 20. Most studies found that the cut-off of 26, suggested by Nasreddine et al 5 to detect MCI in a memory clinic, is inadequate for the stroke setting. The optimal values for normality range from 19 to 22 in studies in which MoCA was administered in the acute stroke phase, 11,12,17,20 and from 20 to 27 in studies in which the test was administered in the chronic phase, 24,27,28,30,[34][35][36] once performances were compared with those on extensive batteries at follow-up.…”
Section: Use Of Moca In the Chronic Poststroke Phasementioning
confidence: 99%
“…23,24 These activities were modulated via effects on geranylated proteins. 23 Our results related to simvastatin doses and hence to serum simvastatin concentrations that corresponded to the low proangiogenic doses in experimental studies. One shortcoming was that we did not measure serum simvastatin concentrations to compare outcomes with the concentrations achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Мы разделили пациентов на группы высокой и низ-кой дозы в соответствии с диапазоном клинических доз, но лечение симвастатином в таких дозах соответс-твовало эффективной концентрации, способствующей пролиферации эндотелиальных клеток, миграции их и дифференцировки в экспериментальных исследо-ваниях двухфазных эффектов низких доз [23,24]. Эти эффекты подвергались модуляции посредством воздействия на геранилированные протеины [23].…”
Section: ■ обсуждениеunclassified
“…A score between 22-26 points suggests a mild cognitive dysfunction, while a score below 22 points, around the average of 16 may indicate a severe cognitive dysfunction, phenomenom of Alzheimer dementia type [5][6][7][8][9].…”
Section: Patient Managementmentioning
confidence: 99%